Sentimento do investidor e a influência do horizonte de investimento em decisões corporativas: evidências baseadas na Teoria de Catering - Miranda, Kléber Formiga (2018)
Based on Catering Theory, this thesis aimed to analyze the effect of the companies’ investment horizon in corporate decisions taken in line with the investor sentiment. The Catering Theory establishes the ability of managers to identify the mispricing occurrence in the stock market, causing decision-making to maintain the difference between the stock price and its fundamental value for the benefit of investors who care about current stock price – short-term investors or short-horizon investment. Assuming the mispricing occurrence when the sentiment index indicates optimism and the following decision-making, based on the sentiment index, the thesis of this study establishes that the investment, financing and earnings management decisions, taken in line with the investor sentiment, aim to cater short-term investors. The firms’ share turnover ratio measured the investment horizon. This study analyzed 245 non-financial companies, listed in B3, through an unbalanced data panel, in the period from 2010 to 2017. Following the theoretical assumption, the relationship between each decision and the investor sentiment was evaluated by simple linear regression estimated by Theil-Sen method, by firm, in order to define the expected value of the decision in function of sentiment. The sentiment index used in the regression was created using variables from the Brazilian capital market, through principal component analysis, based on the existing literature. The variables were incorporated into the index: the number of offerings de IPOs plus Follow-On, Advancing and Declining ratio, dividend premium and individual investor’s participation in the total value of the B3 segment. This latter theoretically associated with the Catering Theory and, the others, traditional in the sentiment literature. The results showed a negative relationship between the investment horizon and the investment decision, contradicting the expectation of H1. There was no relation regarding the earnings management (H3). On the other hand, the financing decision has a negative relationship with the investment horizon, according to H2, suggesting interest for cheaper debts, in optimists’ periods, by firms with short investment horizon (higher Turnover). This fact was corroborated by the disruption of the hierarchy suggested by the Pecking Order Theory (H2a), in which explanatory factors were observed, such as Turnover and ROA for the debt variation. However, it was not possible to associate the motivations for the Pecking Order rejection to the Catering Theory assumptions. In addition to the restricted analysis of the testable hypotheses, it was analyzed the possibility of some firms’ characteristic mediating the relationship between the investment horizon and corporate decisions. In this sense, it was shown that investments are expanding when, beyond the short horizon, firms were more leveraged. When interacting the revenue growth with the investment horizon, there was an increase in the earnings management level. Therefore, despite the rejection of the testable hypotheses H1 and H3, the mediation of the firm's characteristics showed the Catering Theory assumptions. As for the financing decision, besides the non-rejection of the testable hypothesis 2 (H2), there was a reduction in financial expenses in optimist moments when there was the interaction between revenue growth and the investment horizon. Sensitivity tests showed that in other scenarios (not all) these results remain.